INVESTIGATING MARXIST ECOCRITICISM IN AESOP’S SELECTED FABLES - Mashal; Dr. Bushra Siddiqui (International Journal of Contemporary Issues in Social Sciences, 2024)
The study explores Aesop’s selected fables through ecocritical lens by identifying Marxist features of the stories. The stories are famous for the moral lessons they give but other than that, they provide a critique of the writer’s mind and his representation of nature. The stories build up certain power structures based on beliefs of contemporary times which are analyzed in this paper. By debunking ideologies working behind the power structures in the stories their impact and representation of nature is scrutinized leading to the understanding of power dynamics. The research also looks at the story from the perspective of Gaia Hypothesis which binds all the elements utilized in the stories, making them logical and proving the structuring of the fables up to certain extent, correct. The study concludes that the elements used to show the power dynamics, classism and different natural structures are all the working of Gaia Hypothesis.